Prospects and Challenges for Global Natural Gas Market - PETRE PRISECARU; PAUL CALANTER (Global Economic Observer)
The rapidly evolving COVID-19 crisis presents profound challenges for the global natural gas industry, as it does for the energy system as a whole and the economy at large. While LNG prices are collapsing due to oversupply and poor demand, US natural gas productíon and LNG exports may decrease for the first time in a decade. Major Russian gas projects, like Power of Siberia, Turkish Stream, North Stream 2 will increase its exports and competition on China and EU markets.US-China trade war is affecting US exports of LNG to Chinese market, while coronavirus pandemic affects industrial activities and global demand for natural gas. In Europe the influence of mild winter, pandemic and LNG oversupply was obvious and prices have decreased during the first four months. Traditional LNG exporters, such as Qatar, or Middle Eastern producers/exporters were hit by the large surplus on the market and some LNG projects will be postponed. Any demand and price recovery depends on the speed and amplitude of economic recuperation within the global economy.Romania will try to exploit, use and export the important off shore gas reserves, estimated at 200-300 TCM. Taking into considerations all mentioned above, our research has as main objective to presents the major challenges for the future evolution of natural gas market while depicting the main drivers of those challenges. The methodology used is based on an empyrical analysis using both latest international statistics and relevant case studies.